Eugen Habermann (1884–1944) and Herbert Johanson (1884–1964) – from Studies at Riga Polytechnic Institute to the Top of Estonian Architecture - Hallas-Murula, Karin (History of Engineering Sciences and Institutions of Higher Education, 2022)
Graduates of Riga Polytechnic Institute Eugen Habermann (1884–1944) and Herbert Johanson (1884–1964) became the most active architects in Estonia in the 1920s and 1930s. E. Habermann was the City Planning Architect of Tallinn (1914–1923), at the same time, he headed the Construction Board of the Ministry of the Interior (1919–1923). H. Johanson led the project bureau of the City Architect of Tallinn (1924–1944). From 1935, he also ran the Tallinn Municipal Architecture Office. Both architects were the founders of the Estonian Association of Architects (1921) and its chairmen, E. Habermann – from 1921 to 1936 and H. Johanson – in the 1930s. The extensive list of projects of E. Habermann and H. Johanson consists of around 200 projects, including buildings of nearly all types. The article aims to characterize E. Habermann and H. Johanson as personalities based on the memories of their fellows, it also reflects on the main features and stylistic development of their architecture.